‘Indo-Pacific’ vs ‘Asia-Pacific’: Contending Visions? - Chong, Alan (2018)
President Donald Trump’s first extensive visit to Asia in November 2017 ignited a public rivalry between the ‘Indo-Pacific’ and the ‘Asia-Pacific’ frames of diplomacy. However, the ‘Indo-Pacific’ is way behind the ‘Asia-Pacific’ in terms of being tried and tested.